2002
DOI: 10.1039/b202765h
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous separation of inorganic anions and cations using capillary electrophoresis with a movable contactless conductivity detector

Abstract: A number of small inorganic anions and cations were separated after injection of the sample into both ends of a separation capillary. The ions were detected using a capacitively coupled contactless conductivity detector (CCCCD) which could be placed at various positions along the capillary length. Counter-directional migration of anions and cations occurs towards the detector, which is placed at an appropriate position along the capillary so that the migration order is determined by the respective effective se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 33 publications
(41 reference statements)
0
49
0
Order By: Relevance
“…The application to the analysis of rain and surface water samples was demonstrated. Unterholzner et al [54] used the same injection principle for the simultaneous determination of anions and cations in a mineral water sample and demonstrated that fast concurrent determinations of anions and cations can be achieved in less than 75 seconds with a 35 cm long separation capillary. An example for the simultaneous determination of a total of 21 cations and anions [50] is depicted in Figure 7.…”
Section: Simultaneous Determination Of Anions and Cationsmentioning
confidence: 98%
“…The application to the analysis of rain and surface water samples was demonstrated. Unterholzner et al [54] used the same injection principle for the simultaneous determination of anions and cations in a mineral water sample and demonstrated that fast concurrent determinations of anions and cations can be achieved in less than 75 seconds with a 35 cm long separation capillary. An example for the simultaneous determination of a total of 21 cations and anions [50] is depicted in Figure 7.…”
Section: Simultaneous Determination Of Anions and Cationsmentioning
confidence: 98%
“…The method is mainly used for the determination of small inorganic and organic anions and cations, in both conventional [12][13][14][15][16][17][18][19][20] and microchip CE [21][22][23][24], but has also been successfully used for the determination of cyclodextrins [25], underivatized amino acids [26,27], mono-and disaccharides [28], and aliphatic alcohols [29]. Recently, CCD has also been hyphenated to other analytical systems.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is clear that in some cases CE with direct UV detection can be applied for analyzing small ions, authors have focused on solving the sensitivity problem. Some solutions include derivatization prior to UV detection, use of indirect detection, or use of other detectors different from UV, as for instance conductivity [118] or MS [119].…”
Section: Small Organic and Inorganic Ionsmentioning
confidence: 99%
“…Analysis of small ions by CE is also an active area in food analysis [108][109][110][111][112][113][114][115][116][117][118][119]. In general, two main problems have to be solved when analyzing small ions by CE.…”
Section: Small Organic and Inorganic Ionsmentioning
confidence: 99%